A study of analysis and comparison to the low nutrient density foods that more normality for children age (3 –5 years) (Baghdad Science Journal, 2008)
Through the early childhood and after the ablactating the child learns acquired food habbits that might studying with him throughout his life. Here the parents role arises: teaching the child the sound food habits and hygienic styles and whatever beneficial to the health and with the sufficient quantities for the body. In this way the experiences the child learns at home will be of great help in his future life in choosing the suitable food after becoming more dependent in making his decisions and choices away from his parents.The results in this study showed that the averages of the children’s consumption of the high energy foods in comparison with the other highest consumption average , after that comes the con sumption of soft drills , then the lollipops , gums and cacao , finally , the confectioneries recorded the lowest percentage in purchase , the child’s wish recorded the highest average.